Affine density in wavelet analysis - Kutyniok Gitta (Berlin Springer-Verlag, 2007)
This volume provides the first thorough and comprehensive treatment of irregular wavelet frames by introducing and employing a new notion of affine density as a highly effective tool for examining the geometry of sequences of time-scale indices. Many of
Keywords: Wavelets(Mathematics)